The Political Identity: Between Qur'anic View and Western Theory - Sujiat Zubaidi; Aqdi Rofiq Asnawi; Ide Mafaza Sansayto; Humaira Agam Putri (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
Purpose:Identity nowadays has become very complicated in the political sphere. Political identity needs to be studied from two perspectives; Western theory and Islamic theory. Islamic political identity taken from the concept of the Qur'an. This research aims to reveal identity politics from these two perspectives, namely the perspective of the al-Qur'an and Western theory. Method:The library research method is used for this critical analysis research, which takes a qualitative approach. The qualitative method collected data and news references from books, journals, or trusted online sources. Results/Findings:The results show that there are contradictions in interpreting identity politics. Identity politics is often interpreted as something that is considered harmful. Through critical analysis, researchers found differences from the most fundamental aspects of understanding and theory to the value of their influence on society. Conclusion:Even though the theory of identity in the West existed and was developed by Henry Tajfel and John Turner, the theory is in line with how Islam views political identity as necessary as a political strategy that emphasizes differentiation and the utilization of primordial ties as its main category. Identity in the Qur'an is called Shibgah. The theory of identity, both in politics and outside politics, is correct and reasonable.